APOs as promising prognostic biomarkers: correlation with tumor-infiltrating leukocytes in endometrial cancer - Zhou, Lina; Wang, Rencheng; Du, Guiqiang; Wu, Yupeng; Li, Hui; He, Yinyan; Ye, Zhikang; Xiang, Jiangdong (Frontiers in Immunology, 2026)
BackgroundApolipoproteins (APOs) are essentially structural and functional components of lipoproteins, which are composed of 22 members and their effects on certain types of cancer have been studied. However, their roles in endometrial cancer (EC), which is one of the most common malignant tumors in gynecology were unclear and rarely investigated.MethodsWe investigated the expression levels of APOs genes in EC. Furthermore, we explored the roles of APOs in prognostic value, and immune infiltrates in EC patients by using different bioinformatics databases. In-vitro experiments were also conducted to evaluate the effect of APOs genes expression on migrant abilities of EC cells.ResultsNine APO genes (APOC1, APOC2, APOC4, APOD, APOE, APOL3, APOL4, APOLD1, and APOO) were found differently expressed between EC and control tissues by the GEPIA2. However, APOC4 was not included in the subsequent analysis due to its low expression in EC tissues. Moreover, mRNA expression levels of APOs were found correlated with the clinicopathological characteristics of EC, including stage, grade, molecular subgroups, p53 mutant conditions, PTEN mutant conditions, and expression levels of ESR1 and ESR2. Meanwhile higher expression levels of APOs were significantly correlated with better (APOD, APOL3) or poorer (APOC1, APOE, APOLD1) OS. ssGSEA showed 7 TILs in EC which differed significantly from those in adjacent noncancerous tissues were correlated with prognosis of EC patients. The expression levels of both APOD and APOE were positively correlated with all 7 TILs. Finally, western blotting showed that 17β-estradiol (E2) increased APOE protein expression level and reduced APOD protein expression level. Furthermore, APOE was identified to promote the cell migration by scratch assay.ConclusionThe expression of APOs may be a promising prognostic biomarker and is associated with immune invasion as a potential target for endometrial cancer.